More than noise: Employing hip-hop music to inform community development practice. Issue 5 (19th October 2016) - Hollander, Justin; Quinn, Jennifer
Abstract: The quality of information which a community development professional has access to will limit her ability to understand the issues, concerns, and desires of a community. Artistic expression, specifically hip-hop music, can provide a novel level of understanding of community dynamics to community development practice and research. This research established a methodology that would enable practitioners and researchers to effectively extract relevant details embedded within hip-hop music. We employed a microanalysis approach to study 100 hip-hop songs to extract the relevant themes and codes. We found key relationships in the music between the artists and how they relate to their physical surroundings.